Grundtvigs Brorson - Auken, Sune (Grundtvig-studier, 2016)
Grundtvig’s Brorson The article analyzes Grundtvig’s relationship to Brorson’s hymns. It consistsof three parts. The first presents Grundtvig’s limited prose writingsabout Brorson; the second describes what Grundtvig’s versions of Brorson’shymns look like and presents examples of how (and, to an extent,why) Grundtvig makes changes in what Brorson wrote; and the thirdpart analyses Grundtvig’s seven different versions of Brorson’s hymn “ Denyndigste rose er funden” [The lovliest rose has been found]. The articleconcludes with some final reflections on Grundtvig’s practice of revising Brorson’s hymns. It places these revisions in their generic context, comparesthem with Grundtvig’s overall practices as a reviser of hymns, andcautiously points towards their respective roles in later Danish church life.Three accompanying appendixes overview Grundtvig’s rewritings of Brorson’stexts.